“Influence of plasmids, selection markers and auxotrophic mutations on Haloferax volcanii cell shape plasticity” - Patro, Megha; Duggin, Iain G.; Albers, Sonja-Verena; Ithurbide, Solenne (Frontiers in Microbiology, 2023)
Haloferax volcanii and other Haloarchaea can be pleomorphic, adopting different shapes, which vary with growth stages. Several studies have shown that H. volcanii cell shape is sensitive to various external factors including growth media and physical environment. In addition, several studies have noticed that the presence of a recombinant plasmid in the cells is also a factor impacting H. volcanii cell shape, notably by favoring the development of rods in early stages of growth. Here we investigated the reasons for this phenomenon by first studying the impact of auxotrophic mutations on cell shape in strains that are commonly used as genetic backgrounds for selection during strain engineering (namely: H26, H53, H77, H98, and H729) and secondly, by studying the effect of the presence of different plasmids containing selection markers on the cell shape of these strains. Our study showed that most of these auxotrophic strains have variation in cell shape parameters including length, aspect ratio, area and circularity and that the plasmid presence is impacting these parameters too. Our results indicated that ΔhdrB strains and hdrB selection markers have the most influence on H. volcanii cell shape, in addition to the sole presence of a plasmid. Finally, we discuss limitations in studying cell shape in H. volcanii and make recommendations based on our results for improving reproducibility of such studies.